Dedication of a Professional Educative Personnel in Applicing the Independent Curriculum - Hamzah; Nur’aini (MultiTech Publisher, 2023)
Implementation of the Independent Curriculum will not work properly without teachers who have adequate capacity to implement the curriculum. Therefore, this research was conducted to identify and analyze the factors that influence teacher capacity building in implementing the Independent Curriculum. With the idea of the independent learning program by the Minister of Education and Culture Nadiem Anwar Makarim as a form of improving the quality of education in Indonesia, teachers must be able to carry out their duties with full responsibility in carrying out their duties, so that educational goals can run well according to what is aspired to. . To make this happen, teachers must have working professionals from: 1) designing and implementing an independent curriculum, 2) driving teachers and 3) overcoming obstacles to implementing an independent curriculum.